Incidence of asthma in female Swedish hairdressers. Issue 2 (1st February 2002) - Albin, M; Rylander, L; Mikoczy, Z; Lillienberg, L; Dahlman Höglund, A; Brisman, J; Torén, K; Meding, B; Kronholm Diab, K; Nielsen, J
Abstract : Objective: To investigate the risk of asthma in hairdressers. Methods: The incidence of asthma was retrospectively estimated in a Swedish nationwide study including all female hairdressers certified from vocational schools from 1970 to 1995, and a stratified sample of women from the general population were referents. A postal questionnaire included questions on respiratory tract symptoms, atopy, smoking, working periods as a hairdresser, and number of specific hair treatments performed/week. Reported exposures were validated by occupational hygienists. Rate ratios of incidence (IRRs) of asthma were estimated by Poisson regression, adjusted for calendar year of observation, hay fever, smoking, and region of domicile. Results: The crude incidences of asthma/1000 person-years were: 3.9 during active years as a hairdresser, 2.8 among the hairdressers when not working in the profession, and 3.1 among the referents. The corresponding IRR for being an active hairdresser compared with the referents was 1.3 (95% confidence interval (95% CI) 1.0 to 1.6). Moderate effects on risk of asthma were found both from hairdressing work (IRR=1.6 (1.1 to 2.2) among never-smokers) and from smoking (IRR=1.6 (1.2 to 2.2) among referents). However, the combined effect from hairdressing work and smoking (IRR=1.5 (1.0 to 2.1)) was less than expected (p=0.02). No effect modification by respiratory atopy was found. The hairdressers most often performing hair bleaching treatments (IRR=1.5 (0.7 to 3.0)) or using hair spray (IRR=1.4 (0.8 to 2.4)) had, compared with the most infrequent users, a slightly, but not significantly higher incidence of asthma. Exposure to persulphates in hair bleach was estimated to be 0.04–0.15 mg/m 3 during mixing of the powder. Reported average number of bleaching treatments agreed well with those performed according to a diary. Conclusions: Active hairdressing work was associated with a moderately increased incidence of asthma among lifelong non-smokers. The results are moderately supportive, but not conclusive, of associations between asthma and exposure to hair bleach or hair spray.